The effects of COVID-19 pandemic on perceived stress and psychobiosocial states in Italian athletes. Issue 1 (2nd January 2022) - di Fronso, Selenia; Costa, Sergio; Montesano, Cristina; Di Gruttola, Francesco; Ciofi, Edoardo Giorgio; Morgilli, Luana; Robazza, Claudio; Bertollo, Maurizio
ABSTRACT: Italy was one of the most impacted countries by the COVID-19 crisis, with detrimental effects on the world of sports. In this exploratory study, we examined Italian athletes' perceived stress and functional/dysfunctional psychobiosocial states during the COVID-19 crisis, comparing current assessment scores with data collected prior to the pandemic. Differences by gender, sport (i.e., individual vs team sport), and competitive level (elite/expert vs novice athletes) were also examined. The perceived stress scale and the psychobiosocial states scale were administered to 1132 competitive athletes about one month after the beginning of Italian lockdown. The comparison between the data collected during COVID-19 with the data collected before the pandemic outbreak revealed highly significant differences with medium to large effects sizes. Findings suggest that the COVID-19 crisis increased athletes' perceived stress and dysfunctional psychobiosocial states, while decreased functional psychobiosocial states. Analysis of variance revealed significant differences by gender on perceived stress and both types of psychobiosocial states, as well as by competitive level on perceived stress and functional psychobiosocial states. Specifically, women reported higher perceived stress and dysfunctional psychobiosocial states scores than men, and lower functional psychobiosocial states scores. Elite/expert athletes reported lower perceived stress and higher functional psychobiosocial states scores than novice athletes. From a practical point of view, training regimens and healthy behaviours during pandemic crises should be introduced as standard habits for health and well-being. The application of specific well-being protocols for women and novice athletes should be encouraged.